Advice as Practical Epistemology in Multilingual Africa - Projects of The Cluster (Presenting The Cluster Projects, 2021)
Speaking on her short-term project, is Prof. Dr. Susanne Mühleisen, a professor of English Linguistics at the Uni Bayreuth. Her Cluster Project focuses mainly on advice giving and advice receiving in #Cameroon, something, which she refers to as “Practical Epistemology” in her video presentation. Ideally suited is the African context for the collection of data, as it envelops an undeniable multilingualism that has nested itself in all aspects of everyday life. Amongst the initial findings were Dr. Mühleisen’s observations that certain multilingual codes are organised around the very activities of advice, which means that a switch from language to another is triggered in some advice-giving contexts. #epistemology #multilingualism #AfricaMultiple #ClusterOfExcellence #ResearchProject #africa #linguistics #englishlanguage #research #UniBayreuth #bayreuth